Assessing active and passive glenohumeral rotational deficits in professional tennis players: use of normative values at 90° and 45° of abduction to make decisions in injury-prevention programs - Terré, M.; Tlaiye, J.; Solana-Tramunt, M. (Sports, 2025)
(1) Background: Glenohumeral internal and external rotational range-of-movement deficits (GIRDs and GERDs) are some of the primary outcomes used to determine the risk of injury in overhead athletes, such as tennis players. Nevertheless, the current testing position does not consider the fact that most tennis actions are repeated at 45° of abduction, and actively. The aim of this study was to establish normative values of pathological GIRDs and GERDs in tennis players and to provide normative values for both the passive and active rotational range of motion of the glenohumeral joint at 90° and 45° of abduction.